2020
DOI: 10.30595/ratio.v1i1.7974
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Leverage, Likuiditas, Ukuran Perusahaan, dan Fixed Assets Intensity Terhadap Revaluasi Aset Tetap (Studi Empiris pada Perusahaan Aneka Industri yang Terdaftar di BEI Tahun 2014-2018)

Abstract: This study aimed to examine the effect of leverage, liquidity, firm size, and fixed assets intensity on fixed assets revaluation. The sample in this study was a company manufacturing various industry sectors listed on the Indonesian Stock Exchange during 2014-2018 period. Methods of data collection using purposive sampling. The analytical method of research used logistic regression analysis method. These results indicate that the variable leverage has a negative effect on fixed assets revaluation and firm size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
(4 reference statements)
0
0
0
2
Order By: Relevance
“…The results of this study support previous research conducted by Trinita et al (2022) and Fauziah & Pramono (2020), which shows firm size has a positive and significant effect on capital structure. The higher the costs for carrying out operational activities, including labor, the bigger the company.…”
Section: Firm Size and Capital Structure (Leverage)supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study support previous research conducted by Trinita et al (2022) and Fauziah & Pramono (2020), which shows firm size has a positive and significant effect on capital structure. The higher the costs for carrying out operational activities, including labor, the bigger the company.…”
Section: Firm Size and Capital Structure (Leverage)supporting
confidence: 91%
“…Big business is better able to handle business crises (Davidson & Rasyid, 2021). Research conducted by Fauziah and Pramono (2020) shows that company size has a positive effect. So it can be concluded that the company size variables in this study are evenly distributed and do not differ significantly from one another.…”
Section: Firm Size As Control Variablementioning
confidence: 99%
“…Pengaruh Leverage terhadap Revaluasi Aset Tetap. Semakin tinggi tingkat leverage maka semakin rendah kemungkinan perusahaan melakukan revaluasi aset tetap (Fauziah & Pramono, 2020). Leverage yang tinggi menandakan adanya risiko perusahaan melanggar perjanjian utang sehingga perusahaan akan termotivasi untuk menghindari terjadinya pelanggaran ini yang dapat menyebabkan perusahaan kesulitan untuk memperoleh pinjaman dari kreditur.…”
Section: Kajian Teoriunclassified
“…Hal ini menjadi salah satu motivasi bagi perusahaan untuk menggunakan metode yang memungkinkan perusahaannya untuk tidak melanggar leverage convenant untuk menghindari perusahaan kesulitan untuk memperoleh pinjaman dari kreditur akibat meningkatnya risiko kredit perusahaan. Hasil penelitian ini juga tidak didukung oleh (Fauziah & Pramono, 2020) yang menyatakan bahwa leverage berpengaruh signifikan dan negatif terhadap revaluasi aset tetap dikarenakan kreditur lebih tertarik pada jaminan yang sifatnya likuid dibandingkan jaminan berupa aset tetap. Selain itu, leverage yang tinggi menandakan adanya risiko perusahaan melanggar perjanjian utang sehingga perusahaan akan termotivasi untuk menghindari terjadinya pelanggaran ini untuk mencegah kesulitan bagi perusahaan untuk memperoleh pinjaman dari kreditur.…”
Section: Hasil Dan Pembahasanunclassified